Trends in Regulatory Peptides - David Vaudry (Frontiers Research Topics, 2018)
Regulatory peptides represent the most diverse and versatile family of messenger molecules. They are produced by all living organisms from bacteria to mammals. They are involved in a wide variety of biological functions. Biologically active peptides and their receptors thus constitute an unlimited source of inspiration for the development of innovative drugs and cosmetics. The present eBook is a unique collection of research articles and reviews that provide a representative examplification of the latest progress in regulatory peptide research.